Structure-Activity Relationship Study of 8-amino-2,8-dideoxy-β -KDO, a Potent CMP-KDO Synthetase Inhibitor - Adachi, Hayamitsu; Kondo, Ken-Ichiro; Kojima, Fukiko; Umezawa, Yoji; Ishino, Keiko; Kunimoto, Hotta; Nishimura, Yoshio; Akamatsu, Yuzuru (Letters in Drug Design & Discovery, 2008)
8-Amino-2,8-dideoxy-β-KDO is a well-known inhibitor of CMP-KDO synthetase involved in the biosynthesis of lipopolysaccharide (LPS), an essential component of the outer membrane of gram-negative bacteria. Chemical modification of the hydroxyl groups of 8-amino-2,8-dideoxy- β-KDO proved that they play a crucial role in CMP-KDO synthetase inhibition.
Keywords: CMP-KDO synthetase inhibitor